2019
DOI: 10.1080/17429145.2019.1620884
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of MATE transporters and response to metal stress in Cajanus cajan

Abstract: Multidrug and Toxic Compound Extrusion (MATEs) is one of the characteristic transporter families, which plays a key role in the detoxication of endogenous secondary metabolites and exogenous agents in both animal and plant cells. In this study, we identified a total of 67 MATE genes (CcMATEs) from the pigeonpea genome, on which we performed bioinformatics analysis and we group them by phylogenetic analysis. Finally, eight represented CcMATE genes were selected for further qRT-PCR analysis of tissue specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…We discovered 20 MATE-encoding genes from the wheat genome in this study, which can be classi ed into three main subfamilies, which is consistent with previous classi cation of MATE genes in [70] (Fig. 3).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We discovered 20 MATE-encoding genes from the wheat genome in this study, which can be classi ed into three main subfamilies, which is consistent with previous classi cation of MATE genes in [70] (Fig. 3).…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that MATE proteins play an important role in the e ux of plant secondary metabolites, acting as gatekeepers for cells by regulating the in ow of useful substances and the exudation of harmful ones [16]. MATE family genes have been studied in some plant species [33,36,[68][69][70], but not in wheat. Wheat is a protein-rich grain crop.…”
Section: Discussionmentioning
confidence: 99%
“…The MATE transporters are widely conserved in eukaryotic and prokaryotic organisms (Chen et al 2015). Recently, the functions of many MATE transporters have been illustrated in plants (Takanashi et al 2014), including transport of secondary metabolites such as alkaloids (Shoji et al 2009), xenobiotic extrusion (Miyauchi et al 2017), flavonoids (Debeaujon et al 2001), anthocyanin (Pérez‐Díaz et al 2014), detoxification of heavy metals (Li et al 2002, Dong et al 2019), regulation of disease resistance (Sun et al 2011), efflux of plant hormones such as abscisic acid (ABA) (Zhang et al 2014), salicylic acid (SA) biosynthesis (Yamasaki et al 2013), iron translocation (Yokosho et al 2009), aluminum (Al) detoxification (Fujii et al 2012), turgor regulation (Zhang et al 2017), hypocotyl cell elongation (Wang et al 2015), enhanced organ initiation (Burko et al 2011), which indicates the importance of MATE transporters in plants. Owing to these properties, several studies have been conducted to characterize MATE proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike mammalian genomes that carry only a few MATE genes (e.g. 5 in mouse, 11 in human), plant genomes encode a large number of MATE genes, for instance, 56 in Arabidopsis thaliana (Li et al 2002), 53 in Oryza sativa (Tiwari et al 2014), 70 in Medicago truncatula (Zhao and Dixon 2009), 128 in Gossypium hirsutum (Lu et al 2019), 49 in Zea mays (Zhu et al 2016), 48 in potato (Li et al 2019), 67 in tomato (dos Santos et al 2017), 67 in Pigeon pea (Dong et al 2019), 71 in Populus trichocarpa (Li et al 2017) and 117 in soybean (Liu et al 2016). Besides, MATE gene family has also been identified in other plant species such as Sorghum bicolor (Sivaguru et al 2013), wheat (Garcia‐Oliveira et al 2018), Setaria viridis (Ribeiro et al 2017), persimmon (Yang et al 2016), cabbage (Wu et al 2014), Nicotiana tabacum (Morita et al 2009) and Lotus japonicus (Takanashi et al 2013), but no work has been reported in flax ( Linum usitatissimum ) so far.…”
Section: Introductionmentioning
confidence: 99%
“…When the pigeonpea seedlings were 3 weeks old, we selected pigeonpea seedlings with consistent growth status for Al treatment. According to our previous research, we performed Al treatment at a concentration of 50 µM [26]. Samples of roots were collected at 0, 3, 6, and 12 h after Al treatment, frozen immediately in liquid nitrogen, and then stored at −80 • C for RNA isolation.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%